2001
DOI: 10.1021/bc0000987
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Renal Clearance of 111In-Labeled DOTA-Conjugated Antibody Fragments

Abstract: Radiometal-labeled antibody fragments are promising reagents for radioimmunotherapy due to their high tumor uptake and rapid pharmacokinetics, but their therapeutic potentials are limited by high uptake and retention in the kidney. Identification of metabolic products is a first step in designing rationale approaches to lower kidney uptake. Previous studies in rats have shown that 111In-labeled DTPA-conjugated antibody fragments (via lysine residues) were degraded to an DTPA-epsilon-amino-lysine derivative and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 23 publications
3
45
0
Order By: Relevance
“…The molecular mechanism of renal uptake of radiolabeled peptides is not completely understood. High levels of accumulation of radiolabeled polypeptides in the kidneys may be due to the long residence time of radiometabolites produced by lysosomal degradation within renal cells (29)(30)(31). Increased renal uptake could also be attributed to the presence of lysine (32,33), free sulfhydryls, or disulfide bonds in the polypeptide (34).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism of renal uptake of radiolabeled peptides is not completely understood. High levels of accumulation of radiolabeled polypeptides in the kidneys may be due to the long residence time of radiometabolites produced by lysosomal degradation within renal cells (29)(30)(31). Increased renal uptake could also be attributed to the presence of lysine (32,33), free sulfhydryls, or disulfide bonds in the polypeptide (34).…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] It was reported that high renal accumulation of radiolabeled polypeptides and antibody fragments was caused by the long residence time of the radiometabolites produced by lysosomal degradation within the renal cells. 34 -36 Recently, several groups have investigated methods to lower renal radioactivity levels by chemical modification of radiolabeled antibody fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney lysate was prepared as described (31). Briefly, kidneys from normal mice were removed, rinsed with PBS, and homogenized in an equal volume of PBS containing a cocktail of protease inhibitors (Complete tablets, Roche/Boehringer Mannheim, Indianapolis, IN) using a Kinematica homogenizer (Brinkman Instruments, Westbury, NY).…”
Section: Methodsmentioning
confidence: 99%